Esophageal Gastrointestinal Stromal Tumor: Diagnostic Complexity and Management Pitfalls - Charalampos G. Markakis; Eleftherios D. Spartalis; Emmanouil Liarmakopoulos; Evangelia G. Kavoura; Periklis Tomos (Case Reports in Surgery)
Introduction. Gastrointestinal stromal tumors of the esophagus are rare. Case Presentation. This is a case of a 50-year-old male patient who was referred to our department complaining of atypical chest pain. A chest computed tomographic scan and endoscopic ultrasound revealed a submucosal esophageal tumor measuring 5 cm in its largest diameter. Suspecting a leiomyoma, we performed enucleation via right thoracotomy. The pathology report yielded a diagnosis of an esophageal gastrointestinal stromal tumor. The patient has shown no evidence of recurrence one year postoperatively. Conclusions. This report illustrates the complexity and dilemmas inherent in diagnosing and treating esophageal GISTs.